Cardiac Morbidity in an HIV-1 Lipodystrophy Patient Cohort Expressing the TNF-α-238 G/A Single Nucleotide Gene Polymorphism - D. Mahajan, Supriya; Gaekwad, Asmita; Pawar, Jyoti; Tripathy, Srikanth; Ghate, Manisha; Bhattacharya, Jayanta; Om Singh, Hari; A. Schwartz, Stanley; Paranjape, Ramesh; Gangakhedkar, Raman (Current HIV Research, 2015)
In the current study we investigated the prevalence of the TNF-α 238G/A single nucleotide polymorphism (SNP) of the TNF-α gene in the development of lipodystrophy among HIV-1 infected individuals who had been receiving antiretroviral therapy (ART) in the immunodeficiency clinics of the National AIDS Research Institute (NARI) at Pune, India. We assessed the association of this SNP with the development of lipoatrophy/dyslipidemia and insulin resistance in these patients and measured carotid intima thickening which is a surrogate marker for chronic cardiac morbidity. Our results show that the incidence of the TNF-α 238G/A SNP is ∼ two fold higher in patients with lipodystrophy as compared to those without lipodystrophy. Patients with lipodystrophy demonstrated a higher likelihood of the development of metabolic syndrome as evident by increased insulin sensitivity and increased percentage (%) β cell function. Further, a significant increase in left carotid intima thickness was observed in patients with lipodystrophy. Our study validates the association of the TNF-α 238G/A SNP allelic variant with the development of HIV- lipodystrophy via the modulation of TNF-α production, which contributes to dyslipidemia, increased lipolysis, increased insulin resistance, altered differentiation of adipocytes and increased carotid intima thickness. The contribution of genetic determinants such as the TNF-α 238G/A SNP to lipodystrophy, may provide insight into the mechanisms that underlie this disease condition and may be useful in the future for personalized therapy. Additionally, these findings will be useful in monitoring chronic cardiac morbidities among HIV infected individuals who express this SNP.
Keywords: metabolic syndrome